PERANAN WAN SULUNG SEBAGAI PEJUANG KEMERDEKAAN DI SELATPANJANG TAHUN 1945 - Nadila, Siti; Tugiman, Tugiman; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Biography is a way to know the life story of a person through writing. While the role is an activity that has been done by someone in accordance with the status or duty given as well as from this own encouragement. Wan Sulung is a figure that is quite influential in the welfare of society in Selatpanjangin the period of independence and post-independence Indonesia. As a wealthy merchant who is generous no wonder Wan Sulung known enough society. The purpose of this study is (a) to know he short profile Wan Sulung (b) To find out about Wan Sulung efforts as freedom fighters (c) Wan Sulung activities after war of independence in Selatpanjang. This research method is wualitative writing method where the qualitative approach will be able to give a more detailed explanation not obtained from statistical procedure. The result of this research is the eldest Wan Sulung is a rich merchant who has a high social soul. Other than that Badan Penggerak Kemerdekaan Indonesia this Selatpanjang. In addition he is also a member of the independence movement agency in Selatpanjang. Sho he was assigned to Pekanbaru to ensure the truth of Indonesian Indepedence news.Key Words: Role, IndependeAnce